(3GdeNJGQ ef JfHjg GdCNHGQ Ydi eG bjd aj GdefGe ef GdCTYGQs - (3CHh GdYHGS CMeO Hf EHQGgje Hf fUQ Gddg GdcfGfi GdYSbdGfis; (3GdYSbdGfj , CMeO Hf EHQGgje Hf fUQ Gddg YR GdOjf GdcfGfj, CHh GdHQcGJ,J (B876 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi dG jCNPg SfI hdG fhe hdG jMhjg ecGf hdG jZjQg Sfg s
(3BNQgG (B:s
(3Je cJGH GdeNJGQ YeG bjd ai GdefGe ef GdCTYGQ s
(3JfHjg GdCNjGQ GfXQ EjVGM Gdecfhf L(B1 (3U` (B323s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3JYHjQ GdQDjGs